2000
DOI: 10.1021/la991230y
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Force Spectroscopy on Bombyx mori Silk Fibroin by Atomic Force Microscopy

Abstract: A new atomic force microscopy (AFM)-based technique, single-molecule force spectroscopy (SMFS), was used to study the nanomechanics of Bombyx mori silk fibroin. Three types of force-extension curves were found in the system. A modified freely jointed chain (MFJC) model can fit two of the three types well, but the fit parameters are different. The third type of force curve, in which there exists a plateau, cannot be modeled by MFJC. These results may show that there are three kinds of conformations in the silk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 18 publications
5
44
0
Order By: Relevance
“…These events are relatively rare because to complete they require forces of 2e4 nN which are close to the backbone rupture strength [21], thus they can be observed only with very strong tethering of the terminal chains to the AFM tip. The overall shape and force parameters for this type of stretching resemble those observed by Hansma et al [28] and Gaubb et al [31]. In contrast, at intermediate and small stretching distances more organized events were observed which can be associated with the regular unfolding in the protein backbone.…”
Section: Assignment Of Different Stretching Eventssupporting
confidence: 82%
See 2 more Smart Citations
“…These events are relatively rare because to complete they require forces of 2e4 nN which are close to the backbone rupture strength [21], thus they can be observed only with very strong tethering of the terminal chains to the AFM tip. The overall shape and force parameters for this type of stretching resemble those observed by Hansma et al [28] and Gaubb et al [31]. In contrast, at intermediate and small stretching distances more organized events were observed which can be associated with the regular unfolding in the protein backbone.…”
Section: Assignment Of Different Stretching Eventssupporting
confidence: 82%
“…The usual criteria of periodicity, force sequence, shape of a single peak, and appropriate spatial distribution are applied for this selection as will be discussed below. Although the unfolding stretching behavior for different strains was observed for some silk proteins tested in the solid state, the internal domain structure of B. mori fibroin silk protein has not been revealed [31]. For example, good force statistics were observed for spider dragline silk protein unfolding with a primary unfolding length of 14 nm assigned to specific A n G m -type flexible moduli [21].…”
Section: Stretching Strategies For Fibroin Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to get single-molecule characteristic, nice curves were picked and the only last peaks that showed subsequence force dropped to zero were fitted with WLC model. The persistent length was 0.28±0.10nm, which is in a good agreement with persistent length of other proteins such as Bombyx mori silk-like [54], elastin-like [55], spider silk [52], or titin [51]. The contour length was 284±13nm which was slightly less than calculated contour length of S815K molecule (320nm).…”
Section: Resultssupporting
confidence: 80%
“…Li et al were the first to detect differences between silkworm and spider dragline silk and these findings led them to propose a new structural model for SF. AFM studies of silk threads revealed the nanofibril morphology and how the latter was affected by stretching …”
Section: Physical–chemical Characterizationmentioning
confidence: 99%